The social welfare effect of e-commerce product reputation information asymmetry from the perspective of network externality - Min Zhao; Shuyun Wang; Tongshui Xia (PLoS ONE, 2025)
Reputation is the most important intangible asset of merchants. In the e-commerce platform market, reputation information has become an important signal of product quality. However, with increasingly fierce competition among merchants on these platforms, violations of reputation information, such as “click farming,” “cash rebate for favorable comments,” and “pay per click,” have caused information asymmetry and adverse selection. Based on the network externality perspective, considering the duopoly e-commerce platform market, this paper uses game theory to construct a theoretical model to compare and analyze the changes in consumers, merchants, platforms, and social total welfare when the reputation information of e-commerce products is symmetric and asymmetric. The research results show that when the reputation information of e-commerce products is symmetrical, the reputation mechanism of the e-commerce platform can play a positive role, the platform income decreases, and the consumer surplus and the total social welfare level increase. The increment increases with the increase in consumer-side network externality, and the e-commerce platform transfers part of the surplus value to consumers. Due to the influence of network externality, reputation information asymmetry, and violation penalty cost, reputation asymmetry decreases consumer, merchant, and total social welfare and increases platform profits, indicating that the e-commerce platform lacks the economic motivation to govern the violation of reputation information. We recommend that the healthy development of e-commerce platforms proceeds from three aspects: building a reputation mechanism for e-commerce platforms that is jointly supervised by e-commerce platforms, third-party institutions, and social organizations; increasing the cost of punishment for violations; and exerting platform network effects to enhance the competitiveness of enterprises.